Cord Serum Bilirubin Level in Predicting the Development of Significant Hyperbilirubinemia in Newborns with ABO Incompatibility - Arora, Sunita; Shifali, - (Journal of Nepal Paediatric Society, 2016)
Introduction: Neonatal hyperbilirubinaemia is common problem which is benign in majority of neonates. Rh iso immune hemolytic disease as a cause of hyperbilirubinemia is becoming nearly nonexistent due to the use of prophylactic anti D. Hence Isoimmune hemolytic disease due to ABO incompatibility assumes significance as a cause of significant hyperbilirubinaemia. This study was conducted to determine the incidence of ABO incompatibility, ABO iso immune disease in new born, to determine critical cord serum bilirubin level to predict subsequent significant hyperbilirubinemia. Material and Methods: The study was done in neonatal ICU of a tertiary care hospital where 100 full term healthy newborns with B.W≥2500gm and gestational age ≥37 wk with blood group A, B, AB, born to mothers with O blood group without simultaneous Rh incompatibility at SGRDIMSR were included. Serum bilirubin was measured approximately at 12-24hrs, 36-48hrs, 60-72hrs. Results: Out 100 ABO incompatible newborns 33(33%) developed ABO isoimmune disease manifesting as significant hyperbilirubinaemia with any of the four total serum bilirubin levels exceeding threshold levels defined for phototherapy. TSB of ≥ 2.16mg/d1 from cord blood has a sensitivity of 100% specificity of 89.55%, NPV 100% and PPV of 82.50% to predict significant hyperbilirubinaemia. Conclusion: A critical cord S.bilirubin between 2.16 mg/d1 and 4.09mg/d1 will predict all newborns who will have significant hyperbilirubinaemia and can be used as a safe demarcator to decide time of discharge. Any therapeutic intervention if necessary can be started as early as possible. J Nepal Paediatr Soc 2015; 35(3): 231-236